Modelling workplace incivility as a social process towards sustainable workforce in the Malaysian context / S. K. Musairah, Sabiroh Md Sabri and Anis Farhana - S. K., Musairah; Md Sabri, Sabiroh; -, Anis Farhana (Universiti Teknologi MARA, Perlis, 2021)
Twenty years since the concept of workplace incivility has been introduced, research has been conducted in a variety of directions. While the literature has been expanding and it has been reported that as many as 96% employees have experienced workplace incivility and 99% have seen it, we still do not know how employees interpret of workplace incivility. Given that such an interpretation of the social process can affect the future thought and behavior of people, this information is important to understand workplace incivility beyond behavioral description. Although we have a comprehensive conceptual understanding of workplace incivility, without understanding the employees’ beliefs about incivility, we cannot effectively develop an integrative model of workplace incivility. This study aims to develop a model on workplace incivility as a social process that includes interaction during and after the occurrence of incivility at the workplace. In addition, this research also aims to create awareness about workplace incivility; as well as employees' preferences on how to address incivility at work and who should handle it. This qualitative study will investigate workplace incivility to understand incivility from the perspective of employees, refine the theoretical understanding of workplace incivility construct, and collecting data to develop the integrative model of workplace incivility. Employees will be asked to answer open-ended survey questions about the characteristics of workplace incivility and questions about why it happens. Responses will be analyzed with the phenomenological method. This research can also ease the development of practical strategies to manage and prevent workplace incivility. Therefore, the findings of this study can serve as a basis for specific prevention and intervention techniques that can be built in the future. This is because, it is important to uncover effective strategies to manage workplace incivility to improve employee well-being, which in turn would influence organizational performance.